2015
DOI: 10.1016/j.aej.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slip on Herschel–Bulkley fluid flow through narrow tubes

Abstract: A two-fluid model of Herschel-Bulkley fluid flow through tubes of small diameters and slip at the wall is studied. It is assumed that the core region consists of Herschel-Bulkley fluid and Newtonian fluid in the peripheral region. Following the analysis of Chaturani and Upadhya, the equations of motion have been linearized and analytical solution for velocity, flow flux, effective viscosity, core hematocrit and mean hematocrit has been obtained. The expressions for all these flow relevant quantities have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…have [9] have recommended m<100 to get accurate results for viscoplastic materials. A numerical flow study was done for the authors in [10] to determine yield stress's effect on the Herschel-Bulkley fluid's effective viscosity. The Herschel-Bulkley fluids have the following particularity when the particle concentration of the mixture is very high, and the viscosity is large, the forces generated by the interaction and collision of particles lead the fluid to become pasty and indicate the creation of rigid zones.…”
Section: Introductionmentioning
confidence: 99%
“…have [9] have recommended m<100 to get accurate results for viscoplastic materials. A numerical flow study was done for the authors in [10] to determine yield stress's effect on the Herschel-Bulkley fluid's effective viscosity. The Herschel-Bulkley fluids have the following particularity when the particle concentration of the mixture is very high, and the viscosity is large, the forces generated by the interaction and collision of particles lead the fluid to become pasty and indicate the creation of rigid zones.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the material flows with a nonlinear stress-strain relationship once the yield stress is exceeded, either as a shear-thickening fluid or as a shear-thinning fluid. Paints, cement, food goods, polymers, slurries, blood flow, and pharmaceutical products are a few examples of fluids that behave in this manner [29].…”
Section: Introductionmentioning
confidence: 99%
“…The axisymmetric flow of two immiscible, Newtonian fluids driven by a constant pressure gradient in a periodically constricted tube was studied by Fraggedakis et al (2015). Santhosh et al (2015) studied two-fluid model of Herschel-Bulkley fluid in the core region and Newtonian fluid in the peripheral region through small diameters of tubes with slip effect. It was observed that the flow shows abnormal Fahraeus-Lindqvist effect.…”
Section: Introductionmentioning
confidence: 99%
“…Santhosh et al (2015) studied two-fluid model of Herschel–Bulkley fluid in the core region and Newtonian fluid in the peripheral region through small diameters of tubes with slip effect. It was observed that the flow shows abnormal Fahraeus–Lindqvist effect.…”
Section: Introductionmentioning
confidence: 99%